34 Pseudoptosis: Evaluation and Management (Ophthalmic Plastic Surgery of the Upper Face, 2020)
This chapter discusses the diseases and conditions that result in the perceived appearance of blepharoptosis without abnormality of the levator muscle. These periocular disorders result in manifestations mimicking ptosis including decreased vertical palpebral fissure height, deep superior sulcus, and elevated upper eyelid crease. The chapter discusses conditions causing pseudoptosis such as dermatochalasis, vertical strabismus, contralateral eyelid retraction, enophthalmos, ocular abnormalities, and protractor overaction.
Keywords: pseudoptosis; ptosis; superior sulcus; dermatochalasis; enophthalmos; silent sinus syndrome; anophthalmic socket; blepharospasm; hypotropia; orbital fracture